Study on the Effect of Deadman State on Blast Furnace Hearth Erosion Based on Solidification and Melting Model - Fei Yuan; Liangyu Chen; Lei Wang; Lei Zhao; Yan Zhong (IEEE Access)
Blast Furnace (BF) is the primary production equipment for modern ironmaking, and the hearth is a crucial part of the BF where high-temperature molten iron is periodically stored. The deadman, located within the hearth, poses a significant obstruction to the flow of molten iron. Changes in the state of the deadman directly affect the flow and discharge behavior of molten iron within the hearth, subsequently influencing the lifespan of the hearth. This study develops a three-dimensional Computational Fluid Dynamics (CFD) model that incorporates the flow of molten iron and the solidification phase transition within the blast furnace hearth. Using the skull’s thickness in the erosion area as an evaluation index, it investigates the effects of deadman parameters, such as floating height, maximum diameter, eccentricity, porosity, and bottom shape, on the hearth’s erosion area. Additionally, considering the iron flow velocity and furnace wall temperature, the study offers suggestions for the comprehensive protection of the furnace hearth. The findings revealed that maintaining a higher floating height of the deadman is beneficial for the comprehensive safety of the hearth. When the deadman is eccentric towards the erosion direction, its volume increases, or its porosity decreases, the thickness of the skull in the erosion area will decrease, posing potential safety hazards to the operation of the BF hearth. The deadman with a spherical bottom, in both its seated and floating states, results in a stable thickness of the skull in the erosion area, which is favorable for extending the service life of the hearth.